Efektivitas Electronic Module (E-Modul) Promosi Kesehatan untuk Meningkatkan Keterampilan Mencuci Tangan Pakai Sabun pada Anak Usia Sekolah di Panti Asuhan Abul Hasan Jambi - Razi, Pahrur; Surayah, Surayah (UI Scholars Hub, 2023)
Bakground. Poor environmental conditions and not yet good clean and healthy living behavior (PHBS) in the community are suspected to be the cause of the high number of infectious diseases. Various efforts to promote PHBS have been launched by the government to improve people's clean and healthy living behavior. Indonesia is currently facing the problem of the high number of infectious diseases caused by unhealthy behavior, including not washing hands with soap. So there is a need for innovation in introducing and improving the skills of washing hands with soap, such as through health promotion e-modules. Aim. This study aims to determine the effectiveness of health promotion e-modules to improve handwashing skills with soap in school-age children at the Abul Hasan Orphanage, Jambi. Method. The research design used was a Quasi Experiment research design Result. This study found that there was a difference in the mean value of hand washing skills with soap before and after using the health promotion e-module with a p-value = 0.001 (<0.05). The health promotion e-module is more effective in improving the skills of washing hands with soap than using posters, because it meets the Audience, Behavior, Condition and Degree aspects. Conclusion. Health promotion E-Module media is more effective than poster media in improving handwashing skills with soap in school-age children at the Abul Hasan Orphanage Jambi.